#Opinionleaders: a comparison of self-reported and observable influence of Twitter users. Issue 11 (18th August 2021) - Winter, Stephan; Neubaum, German; Stieglitz, Stefan; Ross, Björn
ABSTRACT: Social media have become forums of discussions on political and societal debates in which individual users may forward information or influence others. While prior studies either employed network analyses or surveys to identify opinion leaders and their characteristics, the present investigation combines these two approaches to address the relationship between observable and self-perceived influence. For this purpose, a retweet network of Twitter communication on the Brexit debate ( N = 15, 018) was analyzed in relation to a survey on motives and personality traits that was filled out by a subsample of active users ( N = 98). Results showed that users' eigenvector centrality (as a measure of influence in the network) was significantly related to their political interest and their number of followers, but not to self-perceived opinion leadership. According to a comparison of self-assessment and network position, those with stronger motivations to distribute relevant information tended to overestimate their influence in the network. Implications for the identification of opinion leaders are discussed.